Influence of reactive-ion-etching depth on interface properties in Al2O3/n-GaN MOS diodes. (9th September 2019) - Tokuda, Hirokuni; Harada, Sayaka; Asubar, Joel T.; Kuzuhara, Masaaki
Abstract: Influence of etching depth on the interface properties in Al2 O3 /n-GaN MOS diodes has been investigated. The n-GaN surface was etched by inductively coupled reactive-ion-etching (RIE) with shallow (20 nm) and deep etching (1200 nm) depth. The resulting Al2 O3 /n-GaN interface properties were then evaluated by the capacitance/conductance–voltage ( C / G – V ) and current–voltage ( I – V ) characteristics measurements. It was found that: (i) the interface state density of the shallow-etched MOS diode is almost the same as that of the un-etched reference sample, (ii) the deep-etched MOS diode showed around five times higher interface state density than the shallow-etched MOS diode, (iii) the increased interface state density with deep etching was not recovered by Tetra-Methyl-Ammonium Hydroxide (TMAH) treatment nor by post annealing, and (iv) the deep-etched MOS diode indicated about five orders of magnitude higher leakage current, which could be attributed to the lowering of the effective barrier height in the Fowler–Nordheim type conduction. The results obtained in this study indicate that improved RIE process has to be developed for the fabrication of GaN MOS FETs that require deep etching such as vertical trench-type FETs.